Proyek Irigasi Sollo-Vallei dan Implikasinya bagi Kehidupan Masyarakat Lamongan, 1910-1940 - Silviyana Damayanti; Rhoma Dwi Aria Yuliantri; Muhammad Lingga Andana; Arfaton Arfaton (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
Lamongan Regency is an area that often experiences flooding and drought, which affects crop failure. This condition caught the attention of the colonial government, which at that time was implementing an ethical policy. The Lamongan area affected by irrigation development and improvement was the Bengawan Solo river basin. The Bengawan Solo basin is prone to flooding due to rainwater overflow and often experiences drought during the dry season. To address these problems, the colonial government needed to build irrigation facilities in the form of reservoirs and drainage systems through the Sollo-vallei irrigation project. The Sollo-vallei irrigation project was a water supply system development project aimed at providing water for agriculture and community needs. The Sollo-vallei irrigation project was halted because it required a large amount of money from the colonial government. However, during the construction process in several areas of Lamongan, not everything went well because the water coverage in the limestone area was very low. The existence of the Sollo-vallei irrigation system certainly had an impact on the social and economic life of the Lamongan community, especially on the agriculture of the communities through which the Sollo-vallei irrigation system passed. Even so, the Sollo-vallei irrigation project was not entirely able to overcome flooding due to overflowing water discharge and drought during the dry season. These problems still occur in the Lamongan region, resulting in cases of starvation and poverty due to crop failures. This paper uses historical research methods with several stages, including: topic selection, heuristics, verification, interpretation, historiography, as well as geographical, economic, and social approaches. Thus, this paper shows that during the Dutch colonial period, the Lamongan region experienced development and improvement in irrigation facilities, which aimed to maintain water availability during the dry season, mitigate flooding, and overcome agricultural problems.